The nexus between USAID-funded food security programs and positive peace: a case of Ensure program, Buhera - Besa, Silent T. (Midlands State University, 2018)
This research constitutes one of the first attempts to provide a comprehensive review of the circular relationship between food security and positive peace. It offers some insights on the impact of food security on positive peace and its related development outcomes and how the absence of positive peace contributes to food insecurity. This way it is possible to look beyond income, entitlements or livelihoods related-frameworks as the drivers of food insecurity. Food insecurity can be a result of ineffective governance, lack of sound business environments or low levels of human capital in any given society among other key indicators of positive peace. In countries like Zimbabwe the physical traces of conflict are no longer visible but people are not yet at peace, they are fighting diseases, unemployment, social injustice, abject poverty and in this study food insecurity is identified as another problem denying societies to enjoy positive peace. This stimulates many to ask the question; Even if societies are out of physical/direct violence, does it mean positive peace prevail? Definitely no! Enjoyment of various human needs including food under an environment that ensures human security and development guarantees and builds positive peace. In this study the researcher examined the USAID-funded food security program (ENSURE) in Buhera district in Zimbabwe to find out the factors that binds the nexus in question. USAID-funded programs exhibit some components which strengthen positive peace where it is seen to be absent through their systemic approaches to robustly address the root causes of food insecurity. In the district of Buhera where World Vision is the implementing partner the lack of institutions, structures and attitudes that underpins the existence of positive peace was also identified as the contributing factor to the district’s recurrent food crises. This thesis challenges development agencies, policy makers, NGOs and governments to shift from the broad and historic understanding of peace but thrive to address complex challenges that the world faces today such as food insecurity through the lens of positive peace. Positive peace provides a framework to understand the ideal transformational approaches that can be used for better outcomes in the quest to achieve food security in marginalized and vulnerable communities. Positive peace allowed the researcher to situate the study within the narrow emphasis of people’s well-being or life with quality that any given society desires to have. To the best knowledge of the researcher, no paper has yet provided a detailed survey on the nexus between food security and positive peace in this 21st century.